Pseudophakic Pupillary Block Following Cataract Extraction with Anterior Chamber Lens Implantation : A Case Report: Poster Presentation - Case Report - General practitioner - Sumantra, Ni Putu Sitha Medha Paramitha; Hikmawati, Ike (Majalah Oftalmologi Indonesia, 2023)
Inteoduction : Pupillary block occurs when aqueous humor flow from posterior chamber to anterior chamber is obstructed by functional block between pupillary portion of iris and lens. It is relatively common when pupil is occluded by anterior chamber intraocular lens (IOL). This condition can lead to iris bombe, iridocorneal adhesion formation, increasing intraocular pressure (IOP), and optic nerve damage. Case Illustration : A 65-year-old woman came to local hospital with complaints of blurred left eye five days prior presentation. She had history of bilateral cataract surgery in 2013. On physical examination, BCVA was 6/6 on right eye and 1/300 on left eye. The IOP was 15. 3 on right eye and 31.5 on left eye. Slit lamp examination showed anterior chamber IOL on left eye, shallow camera oculi anterior (COA), no flare/cell, pupillary block was present, and no surgical iridectomy was found. She was previously given timolol 0.5% eye drop and added latanoprost 50 mcg eye drop, sodium chloride 4.4 mg- potassium chloride 0.8 mg eye drop for current therapy. Discussion : Pupillary block is a frequent complication of anterior chamber IOL implantation after cataract surgery. The anterior chamber in this patient was shallow, which indicates partial/total blocked aqueous flow from posterior chamber, causing an elevated IOP, and may disrupt optic nerve that cause decreased vision. Surgical iridectomy is suggested in high-risk procedures such as implantation of an anterior chamber IOL. Conclusion : Elevated IOP may cause visual dysfunction and damage to optic nerve. In cases of high-risk postoperative pupillary block, surgical iridectomy is suggested to prevent further complications